IndiGrid. creating India's first power transmission InvIT / A : - Agarwalla, Sobhesh Kumar, (SAGE business cases., 2020)
The case describes the structure of Infrastructure Investment Trusts (InvITs) created and launched in Indian markets in 2017. As the case illustrates, the aim of allowing these trusts as a pass-through vehicle for tax purposes was to facilitate the direct participation of investors in financing private sector infrastructure investments. Historically, most investments made by the private players in infrastructure sectors in India relied on bank debt and risk capital either brought by the developers or mobilized via equity markets.